Temperature dependence of nitrification in a membrane-aerated biofilm reactor - Németh, András; Ainsworth, Jude; Ravishankar, Harish; Lens, Piet N. L.; Heffernan, Barry (Frontiers in Microbiology, 2023)
The membrane-aerated biofilm reactor (MABR) is a novel method for the biological treatment of wastewaters and has been successfully applied for nitrification. To improve the design and adaptation of MABR processes for colder climates and varying temperatures, the temperature dependence of a counter-diffusional biofilm’s nitrification performance was investigated. A lab-scale MABR system with silicone hollow fibre membranes was operated at various temperatures between 8 and 30°C, and batch tests were performed to determine the ammonia oxidation kinetics. Biofilm samples were taken at 8 and 24°C and analysed with 16srRNA sequencing to monitor changes in the microbial community composition, and a mathematical model was used to study the temperature dependence of mass transfer. A high nitrification rate (3.08 gNm-2d-1) was achieved at 8°C, and temperature dependence was found to be low (θ = 1.024-1.026) compared to suspended growth processes. Changes in the community composition were moderate, Nitrospira defluvii remaining the most dominant species. Mass transfer limitations were shown to be largely responsible for the observed trends, consistent with other biofilm processes. The results show that the MABR is a promising technology for low temperature nitrification, and appropriate management of the mass transfer resistance can optimise the process for both low and high temperature operation.